2013
DOI: 10.1097/aci.0b013e3283624560
|View full text |Cite
|
Sign up to set email alerts
|

Tick bites and red meat allergy

Abstract: Purpose of review A novel form of anaphylaxis has been described that is due to IgE antibody (Ab) directed against a mammalian oligosaccharide epitope, galactose-alpha-1, 3-galactose (alpha-gal). Ongoing work regarding the cause and distribution of this IgE response is reviewed. Recent findings Our recent work has identified a novel IgE Ab response that has been associated with two distinct forms of anaphylaxis: immediate-onset anaphylaxis during first exposure to intravenous cetuximab and delayed-onset anap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 36 publications
2
82
0
4
Order By: Relevance
“…The major allergen is not a protein but a mammalian oligosaccharide and removal of α‐gal dramatically reduces IgE binding to beef proteins 24. Several studies provided evidence that sensitization to α‐gal results from tick bites 11, 12, 25, 26. Consequently, delayed meat allergy is not a consequence of oral but cutaneous sensitization to the α‐gal epitope expressed on proteins present in the gastrointestinal tract of these arthropods 27.…”
Section: Discussionmentioning
confidence: 99%
“…The major allergen is not a protein but a mammalian oligosaccharide and removal of α‐gal dramatically reduces IgE binding to beef proteins 24. Several studies provided evidence that sensitization to α‐gal results from tick bites 11, 12, 25, 26. Consequently, delayed meat allergy is not a consequence of oral but cutaneous sensitization to the α‐gal epitope expressed on proteins present in the gastrointestinal tract of these arthropods 27.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, alpha-gal is present on proteins from epithelia and milk of other mammals (Table 1). 3,4 Some patients might report clinical reactions to dairy, but this does not seem to be widespread. 3,5,6 Abbreviation: alpha-gal, galactose-a-1,3-galactose.…”
Section: Cross-reactivitymentioning
confidence: 93%
“…Onset is typically in adults, although children are not excluded. 4,14 Kennedy et al 18 identified 45 pediatric patients with the allergy. In the United States, red meat typically includes beef, pork, and lamb.…”
Section: Diagnostic Approachmentioning
confidence: 98%
“…In both Australia and the USA, however, large numbers of patients with mammalian meat allergy following tick bites have been identified [8]. In her practice alone, van Nunen has diagnosed over 500 patients (between 1985 and March 2014, with the great majority having presented from 2003 onwards) within a referral base of 440,000 people (1/880), which includes the tick-endemic areas nearby.…”
Section: Central Americamentioning
confidence: 99%
“…In addition, Commins and Platts-Mills [8] have commented that Jappe is said to have identified patients with mammalian meat allergy and cetuximab and alphagal-specific IgE via serological studies and referenced her review of the topic [25].…”
Section: Germanymentioning
confidence: 99%